AKULTURASI DALAM PENDIDIKAN MULTIKULTURAL - Kartina; Ubabuddin (JIP: Jurnal Ilmu Pendidikan, 2026)
Multicultural ethnography in the context of acculturation is an in-depth qualitative research method (ethnography) that focuses on understanding how different cultural groups interact, adapt, and influence each other (acculturation) in a multicultural society. This approach not only describes a single culture in isolation, but also examines the dynamics of social interaction, identity negotiation, and cultural change that often occur when immigrant and ethnic groups meet and live together in the same community. From an Islamic perspective, multicultural ethnography in the issue of acculturation also examines how Islamic teachings interact, adapt, and blend with local cultures without losing their original identity. This approach views Islam as a universal religion, which can be interpreted as a religion that is rahmatan lil 'alamin (a blessing for the universe) by upholding the value of diversity as sunnatullah. Thus, through ethnographic studies, the process of acculturation can be seen in everyday life in the archipelago, resulting in distinctive, inclusive, and moderate forms of Islam.